Penglibatan dan Sumbangan Kanak-kanak Warga Filipina dalam Ekonomi Perikanan di Sabah: Satu Pengadilan Moral? - Ali, Ismail (SOSIOHUMANIKA, 2008)
ABSTRACT: The issues and questions of the existence of Philippine childrenâs in Sabah have been studied and written as well as tried to be solved by the academicians. However, yet the issues and questions are still not being solved but getting worst and putting Sabah at lost. Based on the above question and scenario, the writer thinks that the time has come to stop from discussing and debating the existence of the Philippine childrenâs in various activities in Sabah from the negative perspective, but to change and divert the public perception by looking and defining their involvement positively from global perspective of the current world. In other words, the purpose of this document â based on research, library study and interview â is to provide new breath about the issue and question of Philippine childrenâs and not to repeat what have been studied and written by the previous researcher in realizing and belief that there is a difference and clear dividing line between âfacts and realitiesâ. The purpose of this paper is to discuss the extent and suitability of the involvement of the Philippine childrenâs to be classified as âlabourâ in Sabah fishery economic and to take it as one way of victimization of rights as included in the âConvention of Children Rights 1989â declaration about labour concept as stated in the Sabah Labour Ordinance. However, the Philippine childrenâs (as well as Indonesians) have provided impact in the development of Sabah Economy.Key words:Â  Philippine children, Sabah fishery economy and positive interpretation of historical facts and reality.About the Author: Prof. Madya Dr. Ismail Ali ialah Pensyarah Kanan pada Sekolah Sains Sosial UMS (Universiti Malaysia Sabah) dan Setiausaha Jurnal Sosiohumanika (kongsi penerbitan antara UMS di Kota Kinabalu dengan UPI di Bandung). Beliau dilahirkan di Keningau, Sabah, pada 4hb Mac 1969. Beliau berkelulusan Bachelor of Arts (1991) dan Master of Arts (1999) mengenai sejarah Asia Tenggara dan pengajian sejarah maritim daripada UM (Universiti Malaya) di Kuala Lumpur. Beliau berkelulusan Doctor of Philosophy (2004) mengenai sejarah ekonomi-maritim daripada UMS. Beliau telah banyak menulis buku, di antaranya adalah: Penyalahgunaan Bahan Letupan dalam Industri Perikanan di Sabah (Kota Kinabalu: Penerbit UMS, 2006); dan Pembangunan Industri Hiliran Berasaskan Perikanan di Sabah (Kota Kinabalu: Penerbit UMS, 2007). Bagi urusan sebarang akademik, beliau boleh dihubungi dengan alamat e-mail: ismailrc@ums.edu.myÂ Â How to cite this article? Ali, Ismail. (2008). âPenglibatan dan Sumbangan Kanak-kanak Warga Filipina dalam Ekonomi Perikanan di Sabah: Satu Pengadilan Moral?â in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.1, No.2 [November], pp.365-390. Bandung, Indonesia: Minda Masagi Press, UPI Bandung, and UMS Kota Kinabalu, Malaysia, ISSN 1979-0112.Chronicle of the article: Accepted (June 5, 2008); Revised (August 8, 2008); and Published (November 20, 2008).